USING DATA TO OPTIMIZE HIGHER EDUCATION FINANCING – A MANAGEMENT ISSUE - Daniel BŐJTE (Revista de Management Comparat International)
The financing of higher education is an issue that has long-term societal implications, with a strong political influence and more often than not, hindered by the imperfect competition among HE institutions. The arbitrary way the financing of HE institutions occurs may be mitigated and optimized by using data collection, more precisely an Education Management Information System (EMIS), to ensure precise, fluid and timely datasets. Being not only an IT instrument and a database, but a system within a broader education scheme, EMIS contributes to implementing policies and procedures that efficiently collect, safeguard and use digital data resources to satisfy educational and company requirements. This paper highlights the current status of the financing of HE in Romania, in comparison to other countries, more specifically UK and US.